The Right to Conscientious Objection to Military Service and Turkey’s Obligations under International Human Rights Law - Çinar, Ö. author. aut Link
X, 168 p.
Keywords: This study examines Turkey's non-recognition of the right to conscientious objection to military service and locates this non-recognition within the context of international human rights law - specifically United Nations and European Union system.